The mechanism of oxymatrine on atopic dermatitis in mice based on SOCS1/JAK-STAT3 pathway - Han, Xianwei; Ma, Tianming; Wang, Qiang; Jin, Chunlin; Han, Yusheng; Liu, Guijun; Li, Hao (Frontiers in Pharmacology, 2023)
Based on the suppressor of cytokine signaling 1 (SOCS1)/Janus kinase (JAK)/signal transducer and activator of transcription 3 (STAT3) pathway, the mechanism of oxymatrine in the treatment of atopic dermatitis (AD) was preliminarily explored in this study. C57BL/6 mice were induced to establish AD model by smearing carbotriol (MC903) on their back. The mice were randomly divided into model control group, oxymatrine groups with three dosages (25, 50 and 100 mg/kg), (n=10). Oxymatrine groups were intragastric administered once daily for 14 days. The same volume of saline was given in the normal control group and model group once daily for 14 days. Subsequently, HE staining was used to observe the pathological changes of skin tissue, ELISA was used to detect the levels of serum inflammatory factors including interleukin-4, 6 and 17 (IL-4, IL-6 and IL-17), tumor necrosis factor-α (TNF-α) and immunoglobulin E (IgE). Immunohistochemistry was used to detect the expression of SOCS1 and CD3 in skin tissue, and Western blotting was used to detect the proteins in SOCS1/JAK-STAT3 pathway. Compared with the normal control group, the pathological damage of mice in the model group, such as skin hyperplasia, edema, congestion and inflammatory infiltration, aggravated increased significantly. And the expression of serum inflammatory factors, CD3 positive expression and JAK-STAT3 pathway protein in the model group were increased (P < 0.05), and the expression of SOCS1 protein (P < 0.05) was decreased. Compared with the model group, the above pathological damage of the mice was reduced, and the serum inflammatory factors, JAK-STAT3 pathway protein, and CD3 positive expression were decreased as a dose-dependant manner (P < 0.05), and the expression of SOCS1 protein was increased as a dose-dependent manner (P < 0.05). Oxymatrine can improve the skin inflammation symptoms of AD mice by up regulating the expression of SOCS1, inhibiting the activation of JAK-STAT3 pathway and blocking the activation of T lymphocytes.